2020
DOI: 10.1101/2020.07.18.210211
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibitors of VPS34 and lipid metabolism suppress SARS-CoV-2 replication

Abstract: Therapeutics targeting replication of SARS coronavirus 2 (SARS-CoV-2) are urgently needed. Coronaviruses rely on host membranes for entry, establishment of replication centers and egress. Compounds targeting cellular membrane biology and lipid biosynthetic pathways have previously shown promise as antivirals and are actively being pursued as treatments for other conditions. Here, we tested small molecule inhibitors that target membrane dynamics or lipid metabolism. Included were inhibitors of the PI3 kinase VP… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 56 publications
3
34
0
Order By: Relevance
“…Our data ( Figure S2B) suggest that PI3K type 3 plays a role in an early step of the viral life cycle, such as endocytosis, fusion, translation or early onset of replication. As recently demonstrated by others, treatment of SARS-CoV-2 infected cells with PI3K type 3 inhibitors causes dispersal of the viral N protein and dsRNA throughout the cytoplasm, suggesting a role of this factor in replication complex formation (Silvas et al, 2020). We showed that disruption of the autophagy genes ATG5 and ATG7, which are required for phagophore expansion, does not negatively impact SARS-CoV-2 and HCoV-229E infection (Figure 2E).…”
Section: Discussionsupporting
confidence: 81%
“…Our data ( Figure S2B) suggest that PI3K type 3 plays a role in an early step of the viral life cycle, such as endocytosis, fusion, translation or early onset of replication. As recently demonstrated by others, treatment of SARS-CoV-2 infected cells with PI3K type 3 inhibitors causes dispersal of the viral N protein and dsRNA throughout the cytoplasm, suggesting a role of this factor in replication complex formation (Silvas et al, 2020). We showed that disruption of the autophagy genes ATG5 and ATG7, which are required for phagophore expansion, does not negatively impact SARS-CoV-2 and HCoV-229E infection (Figure 2E).…”
Section: Discussionsupporting
confidence: 81%
“…4c) suggest that PI3K type 3 facilitates an early step of the viral life cycle, such as endocytosis, fusion, translation or replication initiation. Others reported that PI3K type 3 inhibitors cause dispersal of the SARS-CoV-2 N protein and dsRNA throughout the cytoplasm, suggesting a role of this factor in replication complex formation 35 . We showed that disrupting autophagy genes ATG5 and ATG7, required for phagophore expansion, does not block SARS-CoV-2 and HCoV-229E infection (Fig.…”
Section: Articlesmentioning
confidence: 99%
“…Theoretical calculations and practical experimentation alike will be required to develop this technology. [103,104,[196][197][198][199] Spermidine Activator…”
Section: Pharmacological Intervention Targeting Autophagymentioning
confidence: 99%
“…Conclusive studies are still lacking, but potent in vitro inhibition of SARS-CoV-2 replication was recently reported for VPS34-IN1 and VVPS34-IN1 and their analogues, which are inhibitors of vacuolar protein sorting (VPS) 34 (a class III phosphoinositol-3 kinase, PI3K). These inhibitors block autophagy [ 103 , 104 ].…”
Section: The Autophagy-coronavirus Relationshipmentioning
confidence: 99%
See 1 more Smart Citation